Review of Concentrated Solar Power Technology Applications in Photocatalytic Water Purification and Energy Conversion: Overview, Challenges and Future Directions - Cheng Zhang; Na Li; Guangqi An (Energies, 2024)
Photocatalysis, a promising semiconductor-based technology activated by free and eternal solar energy, has great potential for addressing environmental remediation and energy conversion challenges. Concentrated solar power (CSP) technologies, namely parabolic trough reflectors, solar power towers, parabolic dish reflectors and linear Fresnel reflectors, exhibited excellent feasibility for boosting solar-driven photocatalytic processes. Based on the structural characteristics of CSP technologies, the CSP-based photocatalytic reactors could be divided into concentrated types and non/low-concentrated types. This academic review comprehensively investigated the integration of CSP technology in photocatalysis, emphasizing the feasibility of sunlight as an ideal energy source. Additionally, considering the optimal light irradiance and reaction temperature demands for achieving efficient photocatalytic processes, the significance of introducing CSP into solar light-driven photocatalytic reactions was highlighted. Moreover, the current challenges that exist in CSP-based photoreactors were identified, and potential solutions were proposed accordingly. This work hopes to provide some references for the future study of CSP-based photocatalytic reactors under the theme of sustainable development.